Sigmoid colon diverticula perforation associated with sevelamer hydrochloride administration: A case report. (September 2016) - Yamaguchi, Takahisa; Ohyama, Shigekazu; Furukawa, Hiroyuki; Sato, Nariatsu; Ohnishi, Ichiro; Kasashima, Satomi; Kawashima, Atsuhiro; Kayahara, Masato
Abstract: Introduction: Sevelamer is an anion exchange resin used to treat hyperphosphatemia. A common adverse effect of sevelamer is constipation. According to a review of the available literature, colon perforation associated with this resin agent was less common. Presentation of case: A 66-year-old man complaining of lower abdominal pain was transferred to our hospital. The patient had been undergoing hemodialysis for chronic renal failure due to rapidly progressive glomerulonephritis, and had been receiving sevelamer hydrochloride 4.5 g/day for 8years as treatment for hyperphosphatemia. Abdominal computed tomography revealed ascites, free air in the abdominal cavity, multiple diverticula of the sigmoid colon, as well as increased fat tissue surrounding the sigmoid colon. We diagnosed colonic perforation and performed emergency surgery, which revealed a 5 × 5 mm perforation in the sigmoid colon surrounded with soft stool. Histopathologically, sevelamer crystals were detected at the perforation site. Discussion: We theorize that physical stimulation by sevelamer crystals contributed to colon perforation at the already vulnerable diverticulum site. Conclusion: When sevelamer is administered to patients with hemodialysis, the risk of intestinal perforation should be considered. Highlights: Sevelamer may contribute to colonic perforation in hemodialysis patients. Our patient underwent resection of a perforated portion of sigmoid colon. Histopathologically, sevelamer crystals were detected at the site of perforation.